The Influence of Attitude, Perceived Service Quality, Perceived Usefulness, and Trust on Purchase Intention Through Food Delivery Apps Among Generation Z - Nurmaden, Efa Suhadi; Lindiawati, Lindiawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
The purpose of this study is to examine the factors that influence Generation Z's purchase intention in using food delivery applications, focusing on the role of attitude, perceived service quality, perceived usefulness, and trust. Data were collected through an online survey of 200 Generation Z respondents aged 18-26 who had used food delivery applications in the last three months. The results of the analysis using partial least squares structural equation modeling (PLS-SEM) with the help of WarpPLS software show that attitude has a positive and significant effect on purchase intention. In addition, perceived service quality and perceived usefulness have a significant effect on trust, which in turn also has a positive effect on purchase intention. These findings emphasize the importance for service providers to deliver reliable service quality, ensure the usability and convenience of their apps, and build customer trust in order to increase loyalty among Generation Z users. This study contributes to the growing literature on consumer behavior on digital platforms by providing insights into the determinants of online purchase intention in the food delivery service sector.